2013
DOI: 10.1515/jpem-2012-0328
|View full text |Cite
|
Sign up to set email alerts
|

Glucose metabolism in obese and lean adolescents with polycystic ovary syndrome

Abstract: Data on glucose metabolism in Asian adolescents with polycystic ovary syndrome (PCOS) are limited. Glucose metabolism assessment using an oral glucose tolerance test (OGTT) in obese and lean Thai adolescents with PCOS, and a comparison between the two groups were done. Thirty-one patients (19 obese, 12 lean) were enrolled. Their median (range) age was 14.9 (11.0-21.0) years. Eighteen patients had abnormal glucose metabolism (13 hyperinsulinemia, 4 impaired glucose tolerance, and 1 diabetes). Compared between o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Two small studies by Ibanez et al and Silfen et al (52,53) that included 39 nonobese adolescent girls with PCOS failed to demonstrate AGT in any of the subjects. The only study from Asia in 32 Thai (19 obese, 12 lean) adolescents showed that five had AGT (n ¼ 4 IGT and n ¼ 1 DM) (54). These differences may be accounted for by many factors, including, but not limited to, BMI, genetics, family history, dietary practices, and exercise habits prevalent in the community.…”
Section: Discussionmentioning
confidence: 99%
“…Two small studies by Ibanez et al and Silfen et al (52,53) that included 39 nonobese adolescent girls with PCOS failed to demonstrate AGT in any of the subjects. The only study from Asia in 32 Thai (19 obese, 12 lean) adolescents showed that five had AGT (n ¼ 4 IGT and n ¼ 1 DM) (54). These differences may be accounted for by many factors, including, but not limited to, BMI, genetics, family history, dietary practices, and exercise habits prevalent in the community.…”
Section: Discussionmentioning
confidence: 99%
“…Adolescent girls with PCOS have significantly higher rates of perturbations of glucose metabolism, mainly IGT [89][90][91], and are at increased risk of hypertension [92] and MS [89,93], compared to their healthy counterparts. IR and metabolic perturbations are more prevalent in obese than in non obese girls with PCOS [89,91,92] and increased androgens in obese girls with PCOS have been associated with increased cIMT [28].…”
Section: Pcosmentioning
confidence: 99%